Comparison of rotational stability of short and straight stem prostheses in hip arthroplasty : An experimental study - Ghandourah, Suleiman; Justus Liebig University Giessen (My University, 2020)
Background: The rate of hip joint osteoarthritis and associated endoprosthetic replacement is increasing. This is due to the increased life expectancy in modern nations. Additionally, younger patients requiring prosthetic surgery are becoming more prevalent. Straight stem prostheses are well established in the literature and showed good survival rates. However, because of the clinical advantages of short stem prostheses, this study aims to evaluate the biomechanics of the mentioned systems in vitro and to compare the anchoring pattern of straight versus short stems. Methods: A total of 5 systems were examined, Two short and three straight stems prostheses. The examined prostheses included straight stem systems CLS®, EcoFit®, and TrendHip® as well as the short stem prostheses Aida® and Metha®. Each system was implanted in five synthetic femora. Afterward, torque was applied in the ventrodorsal direction continuously with an interval of ± 7Nm. Six inductive extensometers on four measurement levels were utilized to acquire a statement about micromotion between the endoprostheses and synthetic bone. Results: The results showed that all endoprostheses regardless of length exhibited similar anchoring pattern. However, CLS® showed significantly less micromotion (P<0.05) at the proximal measuring point compared to the other systems. All systems registered the lowest relative micromotion at the metaphyseal/diaphyseal measuring point. However, none of the prostheses exhibited significant and quantitatively significant differences in most of the measurements. Therefore, neither the short nor the straight stem endoprostheses had an advantage in rotational stability. The deformation properties between short and straight endoprostheses were comparable. Conclusion: Due to the insignificant differences in anchoring patterns between short and straight stem endoprostheses. The short stem endoprostheses offer a less invasive procedure, require less bone resection and are advantageous in case a revision is needed. These benefits can also be attained by shortening straight stem prostheses. Keywords: straight stem systems, CLS®, EcoFit®, TrendHip®, short stem prostheses, Aida®, Metha®, rotational stability, biomechanics.
Keywords: biomechanics; straight stem systems; CLS®; EcoFit®; TrendHip®; short stem prostheses; Aida®; Metha®; rotational stability; ddc:610